The history of theatre in Anchorage, Alaska 1915-2005 : from a wilderness tent to a multi-million dollar stage - Stadem, Catherine (Edwin Mellen Press, 2009)
The growth of theatre in Anchorage, Alaska, is a microcosm of theatre development throughout the United States in the 20th century. In less than a century, Anchorage grew from its humble origins to become a vibrant frontier city of 300,000 and the cultural center of the state. Homegrown playwrights developed their craft, arts institutions flourished, withered, and were replaced by new institutions. Universities developed cadres of actors, directors, playwrights, designers and technicians. This book contains twelve color photographs and twenty-six black and white photographs.